MENGEKSPLORASI KOMUNITAS PELATIHAN JARAK JAUH BERBASIS INKUIRI DI BALAI DIKLAT KEAGAMAAN JAKARTA - Marina Setiawati (JENTRE, 2022)
This study aims to develop an online learning system for Community of Inquiry (COI) based Classroom Action Research at Jakarta’s Religious Education and Training center (BDK Jakarta). This study uses a qualitative approach with descriptive analysis that has been adapted to the needs and availability of the researcher's time. Learning development refers to the Bates model. Evaluation is executed through expert evaluation and field trials. Furthermore, a test was conducted to obtain data related to increasing the understanding of teacher's concept by analyzing the test and skill’s results. The data obtained from this test indicate that there is a significant increase in understanding the concept. Thus, this inquiry technique community is considered successful in training.